Complete response in metastatic breast cancer with visceral crisis using a combination of cyclin-dependent kinase 4/6 inhibitor and aromatase inhibitor: A case report from the eastern region of India (Indian Journal of Case Reports, 2024)
Patients with metastatic breast cancer (MBC) in visceral crisis require systemic chemotherapy. However, a coexisting cardiac failure that contradicts the use of systemic chemotherapy often demands an alternative treatment. Here, we report a case of hormone-receptor-positive MBC with cardiological comorbidities. She was treated with a combination treatment of tablet Ribociclib (600 mg once daily for 21 days followed by 7 days gap) and tablet Letrozole (2.5 mg once daily). The patient had a complete metabolic response in 18-Fluorodeoxyglucose Positron Emission tomography-Computed Tomography (18F-FDG PET/CT), after 6 months of treatment. Combination treatment with Ribociclib and Letrozole is beneficial in postmenopausal females with hormone receptor-positive and human epidermal growth factor receptor 2 neu-negative MBC in visceral crisis who have a contraindication to chemotherapy.